2015
DOI: 10.1515/amsc-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

Point Movement Trace Vs. The Range Of Mining Exploitation Effects In The Rock Mass

Abstract: The geometric-integral theories of the rock mass point movements due to mining exploitation assume the relationship between the progress of subsidence and horizontal movement. By analysing the movement trace of a point located on the surface, and the influence of the mining exploitation in the rock mass, an equation describing the relationship between the main components of the deformation conditions was formulated. The result is consistent with the in situ observations and indicates the change of the rock mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The use of this solution showed that it predicts values higher than the measured ones and was applied to subsidence with a duration of up to 30 months, i.e., mainly related to phase I and II, rather than to phase III, i.e., residual, long-term subsidence. A similar solution was presented in the article by Hu [44], where authors tried to determine the value of the time factor c of Knothe's function, which relates only to the active subsidence process [45][46][47].…”
Section: Methods Of Forecasting the Residual Subsidence Value After Exploitation Endsmentioning
confidence: 98%
“…The use of this solution showed that it predicts values higher than the measured ones and was applied to subsidence with a duration of up to 30 months, i.e., mainly related to phase I and II, rather than to phase III, i.e., residual, long-term subsidence. A similar solution was presented in the article by Hu [44], where authors tried to determine the value of the time factor c of Knothe's function, which relates only to the active subsidence process [45][46][47].…”
Section: Methods Of Forecasting the Residual Subsidence Value After Exploitation Endsmentioning
confidence: 98%
“…The most important indicator of deformation, from the point of view of threat to civil structures, is horizontal deformation (i.a. Knothe, 1953b;Tajduś and Tajduś, 2015;Sroka et al, 2015;Malinowska and Hejmanowski, 2016).…”
Section: Solved Issuesmentioning
confidence: 99%
“…to the Knothe's definition -i.e. it is some 2.5 times higher than the standard value provided by Budryk. A comprehensive description of the formation of the B factor value studies to date can be found in the works of (Knothe and Sroka, 2010) as well as (Tajduś and Tajduś, 2015) and (Sroka et al, 2015). They are mostly applicable to the dependencies described by the following formulas:…”
Section: Solved Issuesmentioning
confidence: 99%
“…[8][9][10][11]. In the 1950s, Knothe proposed a mining in uence function that conformed to normal distribution according to the observation data [12,13] by treating the surface movement process caused by mining as a random process, Litwiniszyn put forward the random medium theory, arguing that the mining in uence function followed normal distribution as well [14]; In 1965, Liu Baochen and Liao Guohua adopted the probability theory to mathematically demonstrate that the mining influence function conformed to normal distribution, which led to the Probability Integral Method [15][16][17][18][19][20][21][22]. Among the three calculation methods as mentioned above, the Knothe influence function method assumes that the mining influence function conforms to normal distribution based on the observation data.…”
Section: Introductionmentioning
confidence: 99%